(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
In the last decade, European considerations and narratives about the Horn of Africa have been conveyed by the desire to contain the mobility that characterizes the region. However, a more inclusive and less Eurocentric analysis would lead to comprise - and therefore to discuss - the role played by the population growth rates in the different countries of the region in terms of stability and security, potentiality and risk. With this in mind, the family planning programs implemented to control fertility engage local governments, often in partnership with international donors, in long-term challenges. The positive outcomes of such programs are partial, and a stronger action to reach the “demographic peripheries”, where the services and the control of the state diminish, should be implemented. Indeed, the region is facing an interesting population age structure that opens the possibility of a demographic dividend. Nevertheless, it is the management of the population growth, even before mobility control, that may determine, together with an investment in human capital, the positive consequences offered by the demographic bonus, whose potential is influenced by the political, socio-cultural and environmental context.